The Role of Programme “Facing Lithuania” in the KGB Action Plans against “Santara-Šviesa“ - Burinskaitė, Kristina (Genocidas ir rezistencija, 2010)
Struggle with Lithuanians émigré political activity was one of the main targets and aims of the Soviet occupational regime. KGB used a wide range of methods from agent activity to slander actions in the press against the main émigré organizations, their press and the most active personalities. Liberal émigré organization in the USA “Santara-Šviesa”, established in 1957, wished to apply the milder rules for traveling to and back from the Soviet Union as the opportunity for cultural and personal contacts, first of all making closer contacts with the Lithuanian intelligentsia, to know better a situation in Lithuania and to use those connections for transporting illegal literature. Soviet government and KGB wanted to use those connections for neutralisation of political émigré activity, to legalise their power and enlarge the number of their supporters. That is why those contacts were controlled and dictated by the Soviet side, and emigrants, understanding this, tried to escape those traps. KGB saw “Santara-Šviesa” as a threat to the Soviet system, as another organization, however, wanted to use their contacts with the Lithuanians against “Santara-Šviesa”, to split the emigrant organizations and cause damage to the émigré activity. To implement that task, it used such measures like: recruitment of agents, infiltration of agents into the organization, to discredit “Santara-Šviesa” using mass media, propaganda of Soviet achievements as a discredit of émigré activity. Tourism, cultural exchange, personal contacts and other means were used to achieve those targets. Although emigrants stated that they understood and saw the danger and declared that they could resist Soviet propaganda, this research states that it is true just in part, however, KGB could not manage to implement all their tasks.